A study on nutritional status of Anganwadi children in a rural area of North Kerala - Radhamani, K V; Rajeev, S V (Indian Journal of Child Health, 2017)
Background: Malnutrition being the biggest contributor to child mortality and morbidity is highly prevalent among preschool children in India. The state of Kerala which tops the list in most of the health indicators in India is no exception to wide prevalence of malnutrition in children. Objective: To assess the nutritional status of Anganwadi children aged 2-5 years in a rural area of North Kerala. Materials and Methods: A cross-sectional study was done among Anganwadi children between 2 and 5 years of age from January 2013 to March 2013 at Cheruthazham, Kannur district of Kerala. Cluster sampling method was used for the study. Height and weight of the children were measured using the standard anthropometric equipment, and body mass index was calculated. Data were analyzed by SPSS version 17, Microsoft Excel 2007. Results: In accordance with the WHO criteria, 14.6% of children were underweight; 10.6% stunted and 16.6% were wasted. Underweight, stunting, and wasting were most prevalent in 2-3-year-old children and minimum among 3-4-year-old children. Underweight and wasting were more prevalent among female children than their male counterparts. Stunting was more in male children. Conclusion: Results of the present study showed that the nutritional status of the children in studied population was good comparing with other studies. Nutrition, health education and good access, and utilization of healthcare can be very effective interventions which could result in substantial reduction in undernutrition in children.